50‐year anniversary of Lloyd's "mean crowding": Ideas on patchy distributions. (3rd July 2018) - Wade, Michael J.; Fitzpatrick, Courtney L.; Lively, Curtis M.
Abstract: This year marks the 50th anniversary of Monte B. Lloyd's "Mean Crowding" (1967) paper, in which he introduced a metric that accounts for an individual's experience of conspecific density. Mean crowding allows ecologists to measure the degree of spatial aggregation of individuals in a manner relevant to intraspecific competition for resources. We take the concept of mean crowding a step beyond its most common usage and that it has a mathematical relationship to many of the most important concepts in ecology and evolutionary biology. Mean crowding, a first‐order approximation of the degree of nonrandomness in a distribution, can function as a powerful heuristic that can unify concepts across disciplines in a more general way that Lloyd originally envisioned. Abstract : The novelty of this article lies in illustrating mean crowding's utility as a measure fundamental to a large number of different topics in evolutionary ecology.